Mapping the pro-inflammatory epitope of tenascin-C - Alvarez, L (2016)
Endogenous molecules, including extracellular matrix (ECM) proteins, have been shown to induce inflammation via toll-like receptor (TLR) activation in order to drive an immune response to tissue damage. Tenascin-C, an ECM glycoprotein transiently induced in injury and persistently expressed during chronic inflammatory diseases, stimulates cytokine synthesis via activation of TLR4 by its C-terminus fibrinogen-like globe (FBG-C) domain. However, the specific epitope of FBG-C that activates TLR4 is not known. Unlike tenascin-C, other tenascin family members (tenascin-R, -W and -X) are constitutively expressed in healthy adult tissues but also contain a highly homologous FBG domain. I have used comparative analysis of the tenascin family FBG domains to elucidate the molecular mechanism by which FBG-C activates TLR4. The ability of each tenascin FBG domain to activate NF-κB in ThP1 cells and cytokine synthesis in primary human macrophages was assessed. Direct binding to TLR4 was evaluated in vitro using a solid phase binding assay. Peptide mapping and site-directed mutagenesis were used to elucidate specific residues within the FBG domain involved in TLR4 binding and activation. Molecular modelling and docking simulations were performed to analyse the structural basis of the FBG-TLR4 interaction. I've shown for the first time that, in addition to tenascin-C, other tenascin family members (-R and -W) can induce a TLR4 mediated inflammatory response, whereas tenascin-X cannot. The active FBG domains bound directly to TLR4, in the absence of any co-receptor, with low nM affinity. The pro-inflammatory epitope of the FBG domain of tenascins lies in loop 5 in the P-subdomain, where positively charged amino acids are necessary for the activation of TLR4, whilst two other regions in loops 7 and 10 assist in mediating high affinity binding to this receptor. Introducing these sites into FBG-X enabled this domain to bind to TLR4 and to induce an inflammatory response. Together these data revealed how endogenous molecules can induce an immune response and may help in the design of specific inhibitors of TLR stimuli that contain FBG domains.